Preventing violent conflict in Africa inequalities, perceptions and institutions - edited by Yoichi Mine (Houndmills Palgrave Macmillan, 2013)
"Horizontal inequalities are root causes of violent conflict in Africa. Yet, people take actions not because of statistical data on inequalities, of which they might not be aware, but because of injustices they perceive. This volume analyses the results of original surveys with over 3,000 respondents in African cities and towns, exposing clear discrepancies between objective inequalities and people's subjective perceptions. The contributors examine experiences in country pairs and probe into the reasons why neighbouring countries, sharing common historical traits, sometimes took contrasting pathways of peace and violent conflict. Combining quantitative analysis and qualitative anatomy of historical experiences of conflict and reconciliation in Rwanda, Burundi, Ghana, Cote d'Ivoire, South Africa, Zimbabwe, Uganda, Tanzania, Kenya and Nigeria, the study brings forward a set of policy recommendations for development practitioners. This work further addresses the issue of institutional choice and reveals how sustainable power-sharing and decentralisation contribute to political stability in Africa"
Includes bibliographical references
Keywords: Violence--Social aspects--Africa, Sub-Saharan.